Renal denervation in the management of hypertension in adults. A clinical consensus statement of the ESC Council on Hypertension and the European Association of Percutaneous Cardiovascular Interventions (EAPCI). - Barbato, Emanuele; Azizi, Michel; Schmieder, Roland; Lauder, Lucas; Boehm, Michael; Brouwers, Sofie; Bruno, Rosa Maria; Dudek, Dariusz; Kahan, Thomas; Kandzari, David E.; Luscher, Thomas F.; Parati, Gianfranco; et al. (European Heart Journal, 2023)
Since the publication of the 2018 European Society of Cardiology/European Society of Hypertension (ESC/ESH) Guidelines for the Management of Arterial Hypertension, several high-quality studies, including randomised, sham-controlled trials on catheter-based renal denervation (RDN) were published, confirming both the blood pressure (BP)-lowering efficacy and safety of radiofrequency and ultrasound RDN in a broad range of patients with hypertension, including resistant hypertension. A clinical consensus document by the ESC Council on Hypertension and the European Association of Percutaneous Cardiovascular Interventions (EAPCI) on RDN in the management of hypertension was considered necessary to inform clinical practice. This expert group proposes that RDN is an adjunct treatment option in uncontrolled resistant hypertension, confirmed by ambulatory BP measurements, despite best efforts at lifestyle and pharmacological interventions. RDN may also be used in patients who are unable to tolerate antihypertensive medications in the long term. A shared decision-making process is a key feature and preferably includes a patient who is well informed on the benefits and limitations of the procedure. The decision-making process should take (i) the patient's global cardiovascular (CV) risk and/or (ii) the presence of hypertension-mediated organ damage or CV complications into account. Multidisciplinary hypertension teams involving hypertension experts and interventionalists evaluate the indication and facilitate the RDN procedure. Interventionalists require expertise in renal interventions and specific training in RDN procedures. Centres performing these procedures require the skills and resources to deal with potential complications. Future research is needed to address open questions and investigate the impact of BP-lowering with RDN on clinical outcomes and potential clinical indications beyond hypertension.
EVALuna2:525512